Qualities and “Anti-Qualities” of Speech: Representation in Ideographic Dictionary - T. M. Voronina (Научный диалог)
The study of speech from a communicative point of view, namely its communicatively significant qualities, the implementation of the functions of communication and influence, is important primarily in the cultural and speech aspect. Specialists have developed criteria for good speech and requirements for it (informativeness, correctness, accuracy, consistency, relevance, purity, intelligibility, richness, ethics, expressiveness). The purpose of this study is to analyze the specifics of ideas about the qualities of speech in a naive linguistic consciousness. The material of the study is the data obtained in the process of working on the project “Universal Thesaurus of the Russian Language”, which is currently being developed by specialists from the Ural Semantic School under the guidance of prof. L. G. Babenko. Materials from other explanatory and ideographic dictionaries are also used. Among the identified lexemes with the meaning of speech characteristics, first of all, those that are connected by synonymous relations, i.e. are responsible for detailing, concretizing these characteristics. In addition, both compliance and non-compliance with the requirements for good speech, i.e., both its qualities and “anti-qualities”, are marked by linguistic means, which indicates the importance of these opposing characteristics; therefore, attention is also paid to antonymic pairs and groups of words.